Digital Rebranding and Customer Loyalty: Examining the Mediating Role of Brand Awareness and Interaction Quality among Instagram Users in Bali - Christofer Setiawan; Dwi Sih Winarti; Ngurah Gede Dwi Mahadipta (Journal of Social Work and Science Education, 2026)
This study examines the influence of digital rebranding strategy, brand awareness, and digital interaction quality on customer loyalty toward ERSPO, a local Indonesian sports apparel brand, among Instagram users in Bali. A quantitative research design was employed using a purposive sampling technique involving 100 respondents who followed and interacted with ERSPO’s Instagram account. Data were analyzed using multiple linear regression with SPSS version 26. The findings indicate that digital rebranding strategy, brand awareness, and digital interaction quality each exert a positive and significant influence on customer loyalty, with the proposed model explaining a substantial proportion of customer loyalty variance. The study contributes to the digital marketing and brand management literature by providing empirical evidence that integrating digital rebranding initiatives with brand awareness and high-quality digital interactions strengthens customer loyalty in the context of local brands operating in digitally competitive markets. From a managerial perspective, the findings offer practical guidance for companies seeking to enhance consumer loyalty through effective social media branding and engagement strategies. Nevertheless, the cross-sectional design, single-brand focus, and geographically limited sample restrict the generalizability of the findings. Future studies are encouraged to adopt longitudinal designs, include multiple brands and regions, and explore additional variables that may influence customer loyalty.